Potential in vitro anti-allergic, anti-inflammatory and cytotoxic activities of ethanolic extract of Baliospermum montanum root, its major components and a validated HPLC method - Weerachai Pipatrattanaseree; Arunporn Itharat; Nichamon Mukkasombut; Ubonwan Saesiw (BMC, 2019)
Abstract Background The root of Baliospermum montanum has been used as an ingredient of traditional Thai medicines for the treatments of several diseases including itching eczema, muscle and joint inflammation, and cancer. Few studies have been done on phytochemical components of this root. In this study, we isolated major compounds of the crude ethanolic extract of B. montanum root and developed and validated a high performance liquid chromatographic (HPLC) method for the determination of its major components. We then investigated anti-allergic, anti-inflammatory and cytotoxic activities of the extract. Methods The aims of this study were to investigate in vitro activities including inhibitory effect of β-hexosaminidase released from RBL-2H3 cells, inhibition of nitric oxide (NO) production from RAW 264.7 cells and cytotoxic activity against cancerous liver cell lines (HepG2 and KKU M156) by using sulforhodamine B (SRB) assay. Isolation of major components was conducted by using column chromatographic method. Isolated major compounds were analyzed by using high performance liquid chromatography (HPLC). Results The crude extract exhibited the highest cytotoxic activity, with IC50 less than 1 μg/mL, while its anti-allergy and anti-inflammation were also potent with IC50 less than 6 μg/mL. Three propiophenones isolated from B. montanum root exhibited moderate cytotoxic activities (IC50 > 20 μg/mL). Two of the propiophenones found were major components that can be detected by HPLC. The developed and validated HPLC method showed good accuracy, precision, and linearity. Conclusion The results of this study suggested that ethanolic extract of of B.montanum root can be a potential source of anti-allergy, anti-inflammation, and anti-cancer compounds. The isolated compounds can serve as markers when B. montanum is used in herbal remedies but not as overall responsive markers. The HPLC method developed may be useful for quality control in the production of the extract and for further formulation developments. However, investigation of several associated biological activities is necessary before the development can proceed further. Minor active compounds should be isolated and a more sensitive analytical method should be developed to detail the key responsive components of the ethanolic extract of B. montanum root.